(untitled) (Patan Pragya, 2021)
The purpose of this research is to examine the behavior of stock price in Nepalese commercial banks. This research used MPS as dependent variable and experiment variables as EPS, PE Ratio, DY ratio, Size, ROE, BV per share and ROA. The secondary data has been collected from the annual report published by commercial bank for five years’ period from 2015/16 to 2019/20. Descriptive and analytical research design used to analyze and interpret the data using SPSS version 23. Eighteen commercial banks are taken as sample out of 27 population using convenience sampling technique. Multiple linear regression model has used to show the impact of independent variables on MPS. The result indicates that there is a positive and statistically significant effect of EPS, PE ratio and size of bank son MPS. Other variables have negligible effects.